OBSERVASI DATA INTRADAY, KAJIAN ILMU KEPERILAKUAN PADA SAHAM HRTA - Andreas Kiky (STIE Wiyatamandala, 2017)
It is very long story from the beginning of our financial system until the era of information technology. At the first time money was created in order to simplified and made trade more convenient for the human. But through the history the function of money has started to disoriented and changed, not just as tools but also something that signaling our wealth and our wants. Investing nowadays not only worked and transacted very fast and accurate but also made human chasing the money and wealth as the purpose of life. These pheomonema sometimes lead human into heuristic bias in decision making about investment. In some big event such as financial crisis, researcher concludes that might be an error in human decision making. Cause of this error might be the intuitive system of our thinking process. So in this research, researcher wants to examine some signal of behavioral aspect of investor decision making in intraday data.